POLITICAL PARTICIPATION OF MEMBERS OF COMMUNITY ORGANIZATIONS PANCASILA YOUTH IN THE 2024 REGIONAL ELECTIONS IN MAJALENGKA DISTRICT - Syilfa Fakhira; Catur Nugroho (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Regional Head Elections (Pilkada) are a concrete form of people's sovereignty in directly electing leaders. Since the implementation of direct Pilkada, various community organizations have begun to actively participate, including Pemuda Pancasila. This study aims to determine the form of political participation of members of the Pemuda Pancasila organization in the 2024 Pilkada in Majalengka Regency, the factors that influence their participation, and the interaction of this organization with political parties and other mass organizations. This study uses a qualitative approach with a case study method. Data were collected through in-depth interviews, FGDs, observations, and social media documentation. The results of the study show that Pemuda Pancasila plays an active role in campaigns and mass mobilization with a background of organizational solidarity, loyalty to internal leadership, and the influence of local elites. Their participation is also relevant to Huntington's theory of political participation and Watson's behaviorist communication. This study concludes that Pemuda Pancasila's role as a non-party political actor can strengthen or challenge local democratic practices, depending on how they navigate this role within the boundaries of democratic law and ethics.